2006
DOI: 10.1186/1471-2458-6-78
|View full text |Cite
|
Sign up to set email alerts
|

Differences in avoidable mortality between migrants and the native Dutch in the Netherlands

Abstract: BackgroundThe quality of the healthcare system and its role in influencing mortality of migrant groups can be explored by examining ethnic variations in 'avoidable' mortality. This study investigates the association between the level of mortality from 'avoidable' causes and ethnic origin in the Netherlands and identifies social factors that contribute to this association.MethodsData were obtained from cause of death and population registries in the period 1995–2000. We compared mortality rates for selected 'av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 46 publications
5
77
0
10
Order By: Relevance
“…And yet, it is worth noting that the immigrants living in workers hostels and illegal immigrants, likely to be in poorer health, are under-represented, if represented at all, in population-based health surveys, while they contribute to mortality statistics. Other explanations have been suggested by the same authors, namely that migrants would be suffering more from disabling illnesses than from life-threatening illnesses, or die from causes not related to perceived health (Stirbu et al, 2006).…”
Section: Healthy Migrant Effect or Vulnerable Populations?mentioning
confidence: 93%
“…And yet, it is worth noting that the immigrants living in workers hostels and illegal immigrants, likely to be in poorer health, are under-represented, if represented at all, in population-based health surveys, while they contribute to mortality statistics. Other explanations have been suggested by the same authors, namely that migrants would be suffering more from disabling illnesses than from life-threatening illnesses, or die from causes not related to perceived health (Stirbu et al, 2006).…”
Section: Healthy Migrant Effect or Vulnerable Populations?mentioning
confidence: 93%
“…It has been suggested that the health advantages of immigrants diminish at older ages and among the second generation (Sundquist and Winkleby 1999;De Maio 2010); and that these advantages vary substantially by cause of death, country of birth/origin (Stirbu et al 2006;Wild et al 2007;Boulogne et al 2012), and the health measure used (Sundquist and Johansson 1997;Pudaric et al 2003;Llacer et al 2007;Nielsen and Krasnik 2010). While there is a large body of research on health and mortality by migration background, there is a dearth of research examining the health and the mortality of migrants through a gender lens.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…A study of maternal deaths in West Germany from 1980 to 1996 also showed a risk of death twice higher from haemorrhage and from hypertensive disorders in women whose nationality was not German. 9 Data for both studies came from the birth and death certificates of the vital records registry. Classification by cause of death in vital statistics, however, can be imprecise for rare causes of deaths in the industrialised countries.…”
Section: Discussionmentioning
confidence: 99%
“…From 1995 to 2000, immigrants in the Netherlands had a risk of death after childbirth three times higher than women born there. 9 In 2000-2002, black women in the UK had a maternal mortality rate three times higher than did the white women. 10 The reasons for this excess maternal mortality remain unclear.…”
Section: Introductionmentioning
confidence: 99%